D-Dimer and Thrombin-Antithrombin III Complexes in Patients with Clinically Suspected Pulmonary Embolism - Demers, Christine; Ginsberg, Jeffrey S; Johnston, Marilyn; Brill-Edwards, Patrick; Panju, Akbar (Thrombosis and Haemostasis, 1992)
One hundred and fifty-six consecutive patients with clinically suspected pulmonary embolism (PE) had blood drawn to measure levels of D-dimer and thrombin-antithrombin (TAT) complexes and underwent ventilation/perfusion (V/Q) lung scanning and bilateral impedance plethysmography (IPG); pulmonary angiography was performed in 10 patients. Patients were classified as: PE-positive (positive pulmonary angiography or high probability lung scan or non-high probability lung scan and abnormal IPG) or, PE-negative (normal lung scan or normal pulmonary angiography) or PE-unlikely (non-high probability lung scan and normal serial IPG and absence of venous thromboembolism in follow-up). Thirty patients were classified as PE-positive, 64 as PE-negative and 62 patients as PE-unlikely. PE-positive patients were treated with anticoagulants, whereas PE-negative and PE-unlikely patients were not. PE-unlikely patients were followed for 3 months with repeat IPG and clinical evaluation for the occurrence of venous thromboembolism. The sensitivities, specificities, positive predictive values and negative predictive values of the D-dimer and TAT complex assays were calculated for patients classified as PE-positive and PE-negative. In addition, the prevalences of normal D-dimer and TAT complex assays were calculated for PE-unlikely patients.Cutoffs of 300 ng/ml for D-dimer and 3.5 μg/ml for TAT complexes provided sensitivities of 96% for both assays, negative predictive values of 97% for D-dimer and 96% for TAT complexes and specificities of 52% for D-dimer and 51% for TAT complexes. The specificities of the assays were higher in patients without comorbid conditions and in outpatients. Among PE-unlikely patients, 14 had normal D-dimer levels and 5 had normal levels of TAT complexes. None of these patients developed venous thromboembolism in follow-up.Our study indicates that: 1) PE is highly unlikely in patients who have D-dimer levels of less than 300 ng/ml and/or levels of TAT complexes below 3.5 μg/ml, and 2), because of their relatively low positive predictive values, further investigation is required if levels of D-dimer and/or TAT complexes are above these cutoffs. These results should be confirmed in future clinical management trials.